Enhancing Elementary School Students' Motivation to Learn Natural Science (IPA) through the Science, Environment, Technology, and Society (SALINGTEMAS) Learning Model - Astiti, Ayu Dewi; Rashid, Salman; Murni, Yanti; Chaniago, Muhammad Akbar; Irfandi, M. (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2024)
This study aims to increase the motivation to learn Natural Science (IPA) in elementary school students through the Science, Environment, Technology, Society (SALINGTEMAS) learning model. This research was conducted at SD Negeri Sindang III, Majalengka, Indonesia, where the research method used was Classroom Action Research (CAR) with two cycles. In cycle I, meeting II, student learning motivation reached 71%, while in cycle II, meeting II, there was a significant increase to 84%. In addition, observation data of educators' learning actions showed that in cycle I, meeting II the percentage reached 44%, while in cycle II, meeting II, it increased to 78%, exceeding the desired target. Observations of student learning actions also showed an increase, from 66% in cycle I, meeting II, to 88% in cycle II, meeting II, exceeding the target set. Thus, the results of this study indicate that the application of the SALINGTEMAS learning model is effective in increasing the motivation of elementary school students to learn science.